Unintentional Injuries among Under-Five Children in Mid- Western Nepal - Kafle, Bharat; Yadav, Uday Narayan; Marahatta, Sujan Babu; Mishra, Durga; Pant, Narayan Dutt (Journal of Nepal Paediatric Society, 2018)
Introduction: Unintentional injury is the biggest threat to the survival of the under-five children, which impact is immeasurable to families and often entire communities. The objectives of this study were to assess the prevalence of unintentional injuries among under-five children and the factors associated with it. Material and Methods: A facility-based quantitative cross-sectional study was conducted from August 2016 to January 2017. Multistage time frame convenient sampling method was applied to collect the data from 259 mothers of under-five children in the selected district of Mid-Western Development region of Nepal. The data was collected from 10 rural health facilities and two from urban setting using a semi-structured questionnaire. An analysis was performed using SPSS ver.15. Results: The prevalence of unintentional injuries was found to be 33.20 % among the under-five children. The present study showed that ecological belt, the age of mothers, education of mothers, education of fathers, the occupation of mothers, the occupation of fathers, family income quintiles, household type, numbers of a sibling, age and gender of children were significant factors associated with unintentional injuries among under-five children. More than 70% of the respondents were not aware of how to provide first aid care to the children with respect to unintentional injury. Conclusion: This study highlights the burden of unintentional injuries among under-five children in mid-western development region of Nepal. Intervention targeting multifactorial issues in line with all type of fall injuries, burns and injuries with the use of sharp objects might be helpful to tackle the problems.